WHAT WILL CONSTITUTION OF THE STUDENT BODY TELL TO A TEACHER - Nevedomska, Yevheniia O.; Mykhailovska, Anna P. (Educological discourse, 2014)
The article reviews the existing classification of types of constitution of man, set goals and objectives of the experimental study, disclosed method of the experiment. As a result of the study revealed interdependence: between the constitution of the body the man and his temperament, constitution of the human body between introversion and extraversion, between types of temperament and introversion - extraversion. This information will be useful to teachers in the educational process.